Characterization of the complete mitochondrial genome of the nematode-trapping fungus Drechslerella dactyloides - Ling Zhang; Ming-He Mo; Yan-Ru Cao; Lian-Ming Liang (Mitochondrial DNA. Part B. Resources, 2023)
The complete mitochondrial genome of Drechslerella dactyloides was characterized in this study. This mitogenome is a closed circular molecule of 246860 bp in length with a GC content of 26.16%, including 87 predicted protein-coding genes, 29 transfer RNA genes, and two rRNA gens. Phylogenetic analyses based on concatenated amino acid sequences at 14 conserved mitochondrial protein-coding genes showed that D. dactyloides was closely related to Dactylellina haptotyla.